PROFESIONAL KETERAMPILAN SAINS ABAD KE-21 PADA PEREMPUAN PENDIDIK DI KABUPATEN SIAK - Yustina ' (Biogenesis, 2014)
Has conducted research to determine the professional skills of the 21st century science in the district Tualang, Siak Sri Indrapura district in August-September 2013. Determined in consideration of the study sample, the science teacher who taught in class VII Academic Year 2012-2013 as many as 35 teachers from 13 junior high. The research instrument was a questionnaire using a scale covered by the linker. The data analyzed in the frequency, tabulated and analyzed descriptively. The results showed that Min digital age literacy scores of 4.31 (very good). The highest value of 4.63 (very good) that science gathers knowledge from a variety of sources and the lowest value of 3.83 (good) to collect the necessary information science. Literacy effective communication 4.30 (very good), the highest score of 4.66 cooperating (very good) and the lowest value of each act as a leader and member with the value of 3.89 (good) and 3.80 (both) that emotion if not respected. Constraints of women educators in implementing science skills namely: 1) searching for information science skills, 2) skills to act as leaders and members, and 3) the skills to control emotions if not respected.Keyword: science skills, digital age literacy, effective communication, female science teacher educators.